Heritage New Paradigm - Turcanu-Carutiu, Daniela (IntechOpen, 2022)
This Edited Volume "Heritage - New Paradigm" is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of social sciences and humanities. The book comprises single chapters authored by various researchers and edited by an expert active in the social sciences and humanities research area. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on social sciences and humanities and opens new possible research paths for further novel developments.